Intravenous immunoglobulin treatment in women with four or more recurrent pregnancy losses: A double-blind, randomised, placebo-controlled trial - Hideto Yamada; Masashi Deguchi; Shigeru Saito; Toshiyuki Takeshita; Mari Mitsui; Tsuyoshi Saito; Takeshi Nagamatsu; Koichi Takakuwa; Mikiya Nakatsuka; Satoshi Yoneda; Katsuko Egashira; Masahito Tachibana; et al. (EClinicalMedicine, 2022)
Summary: Background: There is no effective treatment for women with unexplained recurrent pregnancy loss (RPL). We aimed to investigate whether treatment with a high dose of intravenous immunoglobulin (IVIG) in early pregnancy can improve pregnancy outcomes in women with unexplained RPL. Methods: In a double-blind, randomised, placebo-controlled trial, women with primary RPL of unexplained aetiology received 400 mg/kg of IVIG daily or placebo for five consecutive days starting at 4–6 weeks of gestation. They had experienced four or more miscarriages except biochemical pregnancy loss and at least one miscarriage of normal chromosome karyotype. The primary outcome was ongoing pregnancy rate at 22 weeks of gestation, and the live birth rate was the secondary outcome. We analysed all women receiving the study drug (intention-to-treat, ITT) and women except those who miscarried due to fetal chromosome abnormality (modified-ITT). This study is registered with ClinicalTrials.gov number, NCT02184741. Findings: From June 3, 2014 to Jan 29, 2020, 102 women were randomly assigned to receive IVIG (n = 53) or placebo (n = 49). Three women were excluded; therefore 50 women received IVIG and 49 women received placebo in the ITT population. The ongoing pregnancy rate at 22 weeks of gestation (31/50 [62·0%] vs. 17/49 [34·7%]; odds ratio [OR] 3·07, 95% CI 1·35–6·97; p = 0·009) and the live birth rate (29/50 [58·0%] vs. 17/49 [34·7%]; OR 2·60, 95% CI 1·15–5·86; p = 0·03) in the IVIG group were higher than those in the placebo group in the ITT population. The ongoing pregnancy rate at 22 weeks of gestation (OR 6·27, 95% CI 2·21–17·78; p < 0·001) and the live birth rate (OR 4·85, 95% CI 1·74–13·49; p = 0·003) significantly increased in women who received IVIG at 4–5 weeks of gestation as compared with placebo, but these increases were not evident in women who received IVIG at 6 weeks of gestation. Four newborns in the IVIG group and none in the placebo group had congenital anomalies (p = 0·28). Interpretation: A high dose of IVIG in very early pregnancy improved pregnancy outcome in women with four or more RPLs of unexplained aetiology. Funding: The Japan Blood Products Organization.